Inward foreign direct investment, superstar firms and wage inequality between firms: Evidence from European regions - Juan David Durán; Iulia Siedschlag (The Economic and Social Research Institute (ESRI), 2023)
Theoretical models and international evidence have established that foreign direct investment is associated with new technologies, productivity gains, higher wages, and wage inequality in the host countries. While most existing studies on foreign direct investment and wage inequality have examined relative wages across skills, occupations and sectors, recent contributions to the theoretical and empirical literature highlight the role of wage dispersion between firms as an important driver of overall income inequality. Against this background, this paper examines wage dispersion between firms across European regions and the role played by multinational firms with dominant market shares, the so-called "superstar firms". Firstly, we document the evolution of wage dispersion between firms and the regional presence of foreign affiliates across European regions. Second, we empirically investigate the role of inward foreign direct investment as a driver of wage dispersion between firms across European regions. The analysis uses firm-level data from the ORBIS Europe data set over 2012-2021 combined with a range of data for European regions. Using a shift-share instrumental variables approach, we find that foreign direct investment, particularly international superstar firms, contributed to increased wage inequality between firms across European regions.
Keywords: F23; R12; R15; 330; Foreign direct investment; Market power; Economic; social and spatial inequalities